On r-duals of some difference sequence spaces - Et, Mikail; Isik, Mahmut; Altin, Yavuz (Maejo Univ, 2013)
In this paper we introduce and examine some properties of the sequence spaces C(Delta(m)(v),lambda,p), C[Delta(m)(v),lambda,p], C-infinity(Delta(m)(v),lambda,p), C-infinity[Delta(m)(v),lambda,p] and V(Delta(m)(v),lambda,p), amd compute the r alpha-, r beta- and r gamma-duals of the sequence spaces l(infinity)(v), c(v) and c(0)(v), and teh r alpha- and rN-duals of the sequence spaces C-infinity(Delta(m)(v)) and C-infinity[Delta(m)(v)].
Keywords: Cesaro sequence spaces; difference sequence; dual space